Brazil's Experience with Agrarian Reform, 1995–2006: Challenges for Agrarian Geography - Fernandes, Bernardo Mançano [UNESP]; Welch, Cliff [UNESP] (SAGE Publications, 2008)
This paper analyses one of the challenges facing agrarian geographers of Brazil: explaining land-tenure systems in light of persistently high levels of land occupations by landless peasants, the implementation of agrarian reform projects by the Fernando Henrique Cardoso (1995–2002) and Luís Lula Inácio da Silva (2003-present) presidential administrations and the expansion of agribusiness. It examines the actions of families organized in the Landless Workers Movement (MST - Movimento dos Trabalhadores Rurais Sem-Terra) and territorialization / deterritorialization processes from 1995 to 2006. We discuss how large land-holding have long determined who holds political power in Brazil and how a “rural block” continues to thwart attempts to resolve Brazil's agrarian question. Consequently, the article concludes, conflictuality is a part of Brazilian rural life that is unlikely to go away.
Keywords: Agrarian Geography; Agrarian Reform Settlements; Land occupation; Land reform; Land-tenure Structure; Landless families - Agribusiness; MST